Novel composite membranes embedded with molecularly imprinted porous polymeric nanospheres for targeted phenol. (11th November 2015) - Ashrafian, Sahar; Ataei, Seyed Ahmad; Jahanshahi, Mohsen
Abstract : In the present research, novel hybrid molecularly imprinted polymer (HMIP) membranes were synthesized for selective adsorption and separation of phenol toxic molecules from aqueous solutions. Molecularly imprinted polymer (MIP) nanospheres for targeted phenol were successfully prepared using precipitation polymerization of methacrylic acid, trimethylolpropane trimethacrylate, and ethylene glycol dimethacrylate, followed by integrating into polysulfone matrix to create the HMIP membranes via a phase inversion method. The fabricated materials were characterized from the viewpoints of spectroscopic analysis, structural and surface morphological properties, porosimetry, and batch rebinding assays. The imprinted polymeric nanospheres with mean diameter value ranging from 210 to 250 nm and average pore diameter of 8 nm were obtained according to the morphological and Brunauer–Emmett–Teller analysis, respectively. Scanning electron microscopy pictures demonstrated that the MIP spheres were uniformly distributed on the surface and in the bulk polymer phase of the hybrid membrane. The surface roughness, porosity, and permeate flux of membrane were significantly augmented by addition of the imprinted polymer particles in the dope solution. HMIP‐2 membrane containing 10 wt% of MIP showed the highest binding capacity and an excellent molecular recognition for phenol with respect to the correlative blank membrane. The selective recognition of phenol on the HMIP‐2 membrane was 3.5 times larger than the analogous compound (i.e. catechol). Moreover, the maximum separation factor of phenol was obtained as 2.19 relative to catechol through selective permeation studies, which was also observed for HMIP‐2 membrane. Copyright © 2015 John Wiley & Sons, Ltd.